2006
DOI: 10.1007/s11156-006-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Role models in finance: Lessons from life cycle productivity of prolific scholars

Abstract: This paper examines the nature of lifecycle intellectual contributions (publication productivity and quality) of prolific scholars in finance, i.e., those that have published twelve or more scholarly papers in finance journals. Like other scholars, their productivity increases dramatically in the years before tenure and early success seems to be a useful forecast of future quality and quantity of publications. However, unlike the average finance Ph.D., these role models begin publishing earlier and they mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…'Highly right-skewed research productivity is not surprising given Lotka's Law of Scientific Productivity' (Berger and Turtle, 2006, p. 21). The Chung and Cox study was, in part, replicated by Aggarwal et al (2007), who studied the output of prolific authors in finance. While Chung and Cox (1990) estimated the Lotka-type ('c') ratio for all finance authors publishing in a large collection of finance journals in the range of 1.95 and 3.26, Aggarwal et al (2007) found it to be 2.47 for prolific authors.…”
Section: Individual Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…'Highly right-skewed research productivity is not surprising given Lotka's Law of Scientific Productivity' (Berger and Turtle, 2006, p. 21). The Chung and Cox study was, in part, replicated by Aggarwal et al (2007), who studied the output of prolific authors in finance. While Chung and Cox (1990) estimated the Lotka-type ('c') ratio for all finance authors publishing in a large collection of finance journals in the range of 1.95 and 3.26, Aggarwal et al (2007) found it to be 2.47 for prolific authors.…”
Section: Individual Contributionsmentioning
confidence: 99%
“…The Web of Knowledge since 2005 has been expanded, and we surmise that it is as good an impact index of journal articles as any. Focusing on the prolific scholars in finance (some of whom are economists) Aggarwal et al (2007) examine the nature of lifecycle contributions -pre-and post-tenure -and envisage that early success is a useful indicator of future productivity in finance. Based on the above brief literature survey, we frame a second proposition, in the null form, as follows: P 2 : JF equivalent output of financial academics tends not to be associated with h-index.…”
Section: Individual Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, if administrators do not invest in faculty who can generate the required prerequisite levels of research, such aspirations are unattainable. Faculty and administrators must also recognize how research productivity and achievement relates to career aspirations and cycles of research achievement as noted by Aggarwal et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al (2002) report that North American institutions dominate the finance literature, although European and Asian institutions are gaining ground. Looking at the life-cycle of prolific scholars, Aggarwal et al (2007) found that frequent, high-quality publishing early in one's career is a good predictor of future productivity. Additionally, Chan et al (2007) provide rankings of research output by country based on 21 journals.…”
mentioning
confidence: 99%